Technology of irreversible electroporation and review of its clinical data on liver cancers. (1st February 2018) - Cohen, Emil I.; Field, David; Lynskey, George Emmett; Kim, Alexander Y.
ABSTRACT: Introduction : Irreversible electroporation (IRE) has developed as a novel percutaneous ablative technique over the past decade and its utility in the treatment of primary and metastatic liver disease has progressed rapidly. Areas covered : After discussing the principles behind the technology and the practical steps in its use, this article offers a detailed analysis of the recent published work that evaluates its safety and efficacy. The strengths and weaknesses of other ablative techniques, including radiofrequency ablation, microwave ablation and cryoablation, are discussed in detail. Other aspects of IRE, including post-treatment clinical follow-up, expected imaging findings, and the most frequently encountered complications, are covered. Finally, the future of IRE is examined as it pertains to advancements in the treatment of hepatic malignancy. Expert commentary : The characteristics of IRE that make this technology uniquely suited for the treatment of liver tumors have allowed it to gain a significant foothold in interventional oncology. Continued development of IRE will lead to further advances in the management of previously untreatable liver cancers.